2010
DOI: 10.1111/j.1365-2435.2010.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and the timing of breeding in a long‐lived bird: a role for stress hormones?

Abstract: Summary1. Young birds often reproduce later in the season than older ones, with poorer breeding success, but the proximate mechanisms involved in such a pattern remain poorly studied, especially in long-lived species. One possible mechanism is the endocrine stress response which is accompanied by the release of corticosterone. Elevated corticosterone levels can trigger physiological and behavioural responses that may delay or even suppress reproduction. 2. We tested the hypothesis that the delayed timing of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 69 publications
(157 reference statements)
5
57
0
Order By: Relevance
“…Furthermore, the low P4 and T levels in deferring birds is a hormonal profile that has 297 been linked to poor condition in seabirds [13,14,15]. These finding support our first prediction: 298 breeding deferral is characterized by low body mass, low blood hematocrit, and a generally 299 compromised condition upon arrival at the breeding colony after overwinter migration.…”
Section: Vitellogenesis 289supporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, the low P4 and T levels in deferring birds is a hormonal profile that has 297 been linked to poor condition in seabirds [13,14,15]. These finding support our first prediction: 298 breeding deferral is characterized by low body mass, low blood hematocrit, and a generally 299 compromised condition upon arrival at the breeding colony after overwinter migration.…”
Section: Vitellogenesis 289supporting
confidence: 56%
“…The initial breeding decision (breed/defer) was very strongly associated 316 with body mass, independent of age or quality, and the simplest explanation for this pattern is 317 that returning females can assess their post-migratory physiological state, and if some relative 318 threshold of condition has not been attained they will forgo reproduction thereby minimizing 319 fitness costs (as per life-history theory, [29]). This might be mediated in part by the effect of 320 body condition on hormonal processes which affect HPG functioning [13,14,15], and in our study 321 P4 and T were not up-regulated in deferring females to a degree that would support gamete 322 production. Previous studies of carryover effects in migratory animals, including seabirds, 323 provide some evidence for this by arguing that the environmental conditions experienced during 324 the non-breeding period can influence resource state at the onset of reproduction ([16] and 325 references therein).…”
Section: Resource-dependent Breeding Decisions 313mentioning
confidence: 55%
See 1 more Smart Citation
“…In birds, chronic stress can reduce body condition [37,38] and thus, it is probable that birds stressed by captivity eventually ended their spring staging period with reduced body condition. If the elevated corticosterone levels associated with the acute stress of capture persisted for some time [39], it could also have deleterious effects on the reproductive physiology and behaviour [40,41]. For instance, Goutte et al [41] found that elevated levels of baseline corticosterone during the pre-laying period were associated with a higher probability of skipping breeding in female snow petrel (Pagodroma nivea).…”
Section: Naomentioning
confidence: 99%
“…If the elevated corticosterone levels associated with the acute stress of capture persisted for some time [39], it could also have deleterious effects on the reproductive physiology and behaviour [40,41]. For instance, Goutte et al [41] found that elevated levels of baseline corticosterone during the pre-laying period were associated with a higher probability of skipping breeding in female snow petrel (Pagodroma nivea). Our experimental design also manipulated males because they were maintained in captivity for the same length of time as females (though all of them received ad libitum food) to ensure that mates could reunite upon release.…”
Section: Naomentioning
confidence: 99%